2015
DOI: 10.1111/edt.12250
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of viable Enterococcus faecalis in human radicular dentin treated with 1% cetrimide and conventional intracanal medicaments

Abstract: Both 1% CET and TRIA significantly reduced the viability of E. faecalis in dentine of extracted teeth in comparison with 2% CHX gel and calcium hydroxide paste. Further laboratory and clinical investigations should be carried out to validate findings of the beneficial use of 1% CET as an intracanal medicament against E. faecalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…In biofilms treated with 2% CHX, a mixed population of green, yellowish green and red-labelled cells was observed indicating that CHX is less effective against biofilm cells. Our CLSM findings are in agreement with previous studies [37,38], which showed apparently live cells after 24 h treatment with 2% CHX. The limited ability of CHX to disrupt attached biofilms is well known [39], and could be attributed to its potential fixative action [40].…”
Section: Discussionsupporting
confidence: 93%
“…In biofilms treated with 2% CHX, a mixed population of green, yellowish green and red-labelled cells was observed indicating that CHX is less effective against biofilm cells. Our CLSM findings are in agreement with previous studies [37,38], which showed apparently live cells after 24 h treatment with 2% CHX. The limited ability of CHX to disrupt attached biofilms is well known [39], and could be attributed to its potential fixative action [40].…”
Section: Discussionsupporting
confidence: 93%
“…The efficacy of endodontic therapy is closely tied to the efficient elimination of bacterial colonization within the pulp cavity. 36 Hence, the incorporation of antibacterial agents, intracanal irrigants, and medicines plays a pivotal role in eliminating remaining microorganisms and attaining a desirable outcome in the context of root canal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The probiotic strain was found to colonise the oral cavity of subjects in as early as three months, and then gradually declined to extremely low levels by 12 months. Altogether, the findings show that the daily use of probiotic L. paracasei SD1 strain may be suggested in children who are at an elevated risk of caries to reduce the number of Streptococcus mutans accountable for the early phases of dental decay [ 22 ].…”
Section: Discussionmentioning
confidence: 99%